Soft Collagen-Gelatine Sponges by Convection Drying - Meyer,Michael (2015)
This study showed that thermally labile fibrillar collagen could be processed continuously in combination with gelatine as foaming additive by convection drying. The procedure led to stable sponges with similar structural and physical properties as found for freeze-dried collagen samples. The fibrillar collagen remained native, while gelatine acted as foaming additive. The absorbency of the sponges was improved by opening the surface with abrasives. A use as medical device with hemostyptic properties would be possible.